TINDAKAN SOSIAL PEMUDA DALAM PELESTARIAN TRADISI BERSIH DESA DI ERA MODERNISASI (STUDI KASUS DUSUN SIWAL, KECAMATAN GONDANGREJO, KARANGANYAR) - Rahmadhani, Melva Novianda; Trinugraha, Yosafat Hermawan (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
This study aims to examine the social actions of youth in preserving the village clean tradition in Siwal Hamlet, Gondangrejo District, Karanganyar Regency, amidst the flow of modernization. The Village Clean Tradition is an intangible cultural heritage that contains spiritual, social, and cultural values. However, modernization and the influence of foreign cultures have begun to erode the participation of the younger generation in local traditions. Through a descriptive qualitative research method, data were collected through interviews, observations, and documentation of the implementation of the village clean tradition in Siwal Hamlet. The results of the study indicate that with community efforts to involve youth in the implementation of the village clean tradition, it can be a means to preserve culture amidst the flow of modernization. Despite the challenges of modernization, the youth in Siwal Hamlet remain active, participating in the village clean activity. The actions of these youth not only maintain the sustainability of local traditions but also strengthen the sense of solidarity and cultural identity of the local community. This study emphasizes the importance of the role of youth as agents of change who can bridge tradition and modernization for the sustainability of local traditions